Re-viewing D-Day: The cinematography of the Normandy landings from the Signal Corps to Saving Private Ryan. (April 2015) - Binns, Daniel; Ryder, Paul
In that it privileges the grand perspective (the landscape, and the battalion arrayed in all its splendour), The Longest Day (1962) is typical of big-picture World War II films produced up until the mid-1970s. There are few close-ups, and takes are ponderously long. The focus is on grand strategy, and an attendant grand narrative; the lens offers a blow-by-blow assessment of the massive assault. Shot in 1998, Saving Private Ryan periodically echoes this perspective but reflects modalities informed by changing technologies and a hyper-mediated culture. The result is more intimate framing, punctuated by shots sometimes adapted from the source material: footage captured on Omaha Beach, 6 June 1944, by the Signal Corps cameramen. This portrayal serves two purposes: it opens the film in spectacular fashion, introduces the main characters and prefaces their mission. This article identifies and examines filmic frames from the day of the landings; from the grand narrative of The Longest Day ; and from Spielberg's confronting representation Saving Private Ryan . The aim is to show how, through the lens alone, cinematographers approximate the character of a tumultuous and terrifying day in ways that are surprisingly similar and profoundly different.